Wave energy potential and 1–50 TWh scenarios for the Nordic synchronous grid. (February 2017) - Ayob, Mohd Nasir; Castellucci, Valeria; Waters, Rafael
Abstract: This study estimates the wave energy potential along the coasts of the Nordic countries with the Nordic synchronous grid as a chosen boundary. A model for wave farm allocation was developed and applied to achieve annual energy production targets of 1 TW h, 3 TWh, 10 TWh and 50 TWh. The study is based on 10 years of data, from 2005 to 2014, from the European Center for Medium-Range Weather Forecasts. Data from a total of 728 coordinate points along the Nordic countries, with a 0.125° × 0.125° spatial resolution, were considered. An algorithm was developed to generate the scenarios, to estimate the installed capacity of wave farms at different locations along the coasts, and to measure the physical space required by the farms. This analysis of the four energy target scenarios resulted in a required installed capacity of 337 MW, 1.02 GW, 3.42 GW and 17.09 GW, covering a stretch of the total coast of 0.4, 1.2, 3.8 and 18.9% respectively. The total annual wave energy resource for the Nordic countries is determined at 590 TWh, most of which is available along the Norwegian coast. Graphical abstract: Highlights: We analyzed the wave energy potential along the coasts of Nordic countries. A model for wave farms allocation for energy scenarios of 1, 3, 10, 50 TWh was developed. The four energy target scenarios resulted a required install capacity of 337 MW, 1.02 GW, 3.42 GW and 17.09 GW.